Exploring the Role of Edge-AI in Autonomous Vehicle Decision-Making: A Case Study in Traffic Management (International Journal of Scientific Research and Management (IJSRM), 2021)
The rapid evolution of autonomous vehicles (AVs) has highlighted the need for efficient, real-time decision-making systems to address the complexities of modern traffic management. Edge artificial intelligence (Edge-AI), which processes data at or near the source of collection, offers transformative potential in this domain. This article explores the role of Edge-AI in enhancing AV decision-making, emphasizing its ability to overcome latency, connectivity, and scalability challenges associated with centralized AI systems. Through a case study in an urban traffic management setting, we examine how Edge-AI enables AVs to make instantaneous decisions, integrate seamlessly with existing infrastructure, and optimize traffic flow. Key findings demonstrate significant reductions in congestion and improved safety metrics, underscoring the viability of Edge-AI as a cornerstone of future mobility solutions. The discussion also addresses technical, ethical, and regulatory challenges while highlighting emerging opportunities such as 5G and IoT integration. This study aims to provide a comprehensive understanding of Edge-AI’s potential to revolutionize traffic systems and pave the way for smarter, safer, and more efficient urban mobility.